Realization of energy harvesting and temperature indication functions for zero-energy thermos flask. (15th October 2022) - Chien, Chih-Cheng; Lin, Po-Hung; Chiang, Chih-Chan; Chen, Yu-Bin
Abstract: A zero-energy thermos flask with energy harvesting and temperature indication functions is demonstrated in this work. Firstly, a phase change material and wavelength-selective transmitting polymer wall are adopted together to harvest solar heat via the greenhouse effect. Next, two thermochromic pigments are utilized for temperature indication. The displayed color pairs can represent fluid status as hot (>338.15 K), warm (328.15 K–338.15 K), or lukewarm (<328.15 K). Indicating temperature both assures the users' safety and specifies the best time having a hot drink. A numerical model is constructed for dimension optimization using the Taguchi method. A prototype of zero-energy thermos flask is then generated for experimental demonstration. Transient thermal analysis is also executed with aids from numerical modeling. Graphical abstract: Image 1 Highlights: Energy harvesting and temperature indication are realized without energy consumption. Both the thermochromic materials and thermal energy storage material are developed. A prototype of thermos is generated with optimal dimensions for proof-of-concept.